A helical shape of polyoxypropylene chain for extended surfactant molecule at the water/oil interface: Theoretical and experimental study. (15th March 2022) - He, Hong-Jia; Xiao, Hongyan; Cao, Xu-Long; Yuan, Fu-Qing; Jiang, Xiang-Dong; Zhang, Lei; Zhang, Lu; Zhao, Sui
Highlights: A helical shape of long polypropylene chain in a row of 4 units at the water/oil interface was proposed. A new method to analytically describe the detailed interfacial alignment of long polypropylene chains was used. Long enough polypropylene chain played an important role in producing the ultralow interfacial tension. Abstract: With all-atomic molecular dynamics method, we investigated the molecular array behaviors and dynamic properties of extended surfactant: alkyl polypropylene (PO) ether sulfonate (APS) at the water/oil interface. Detailed simulation results, including interfacial thickness, stretch degree and tilt angle, all indicated that the long PO chain curled near-evenly in a row of 4 PO units at the interface on low concentration and then stretched out to achieve tight alignment on high concentration. Based on the simulation results, we proposed a helical shape of long PO chain mechanism at the water/oil interface. Furthermore, the experimental results demonstrated that long enough PO chain played an important role in adjusting the size of hydrophobic group and producing the ultralow interfacial tension, which is in good agreement with the simulation analysis. This study will improve the design and synthesis of more efficient extended surfactants in enhancing crude oil recovery.